PULSE PRESSURE CLASSES AND FREQUENCY OF USE OF SEPARATE GROUPS OF CARDIAC DRUGS IN PATIENTS BEFORE AND IN THE EARLY PERIOD AFTER PACING - Pochinska, M.V.; Shevchuk, M.I. (World of Medicine and Biology, 2018)
Pulse pressure (PP), which is determined by the difference between systolic and diastolic arterial pressure, depends on the degree of tone of the arterial walls and the left ventricular (LV) pumping function. PP beyond physiological values (40-60 mm Hg) increases the risk of cardiovascular complications and overall mortality.Permanent pacing, which is used to treat patients with rhythm and conduction disorders, as well as chronic heart failure (CHF), requires modification of the drug therapy that, in turn, affects the change in PP. However, changes in the frequency of the appointment of the main groups of cardiac drugs in the classes of PP in patients in the early period after pacemaker implantation in the literature have not been studied.In the proposed manuscript, the frequency of appointment of individual groups of cardiologic drugs depending on the PP classes in the early period after pacemaker implantation in 220 patients (110 men and 110 women) at the age of 70 ± 9 years was studied. Among the indications for the cardiac pacing were atrioventricular blockade, His bundle branch block, syndrome of weakness of the sinus node, constant bradysystolic form of atrial fibrillation and dilated cardiomyopathy. Exclusion criteria were: age less than 40 years, presence of concomitant angina pectoris IV functional class (FC), CHF IV FC, stimulation of the right ventricular and / or LV less than 50% throughout the observation period. Medication therapy was represented by the following means: anticoagulants (warfarin, pradaxa, ksarelto), antiagregants (clopidogrel, acetylsalicylic acid), antiarrhythmic drugs (amiodarone); β-adrenoblockers (metoprolol, bisoprolol, nebivolol, carvedilol), diuretics (hydrochlorothiazide, furosemide, thorassemide), antagonists of Ca (amlodipine, nifedipine and verapamil), angiotensin-converting enzyme (ACE) inhibitors (enalapril, lysinopril, ramipril), angiotensin II receptor antagonists (ARA II) (losartan, candesartan). Patients were classified into five classes of PP: I - very low PP - less than 20 mm Hg, II - lower than 20 - less than 40 mm Hg, III - normal - 40 - 60 mm Hg, IV - high above 60 - less than 80 mm Hg, V - very high PP - more than 80 mm Hg. The frequency of appointment of the listed medicines in the early period after the pacemaker implantation in each PP class was determined. The results were processed after the database was created. Statistical processing was performed using Microsoft Excel (for nonparametric data: absolute (n, number) and relative (p, %) units). Statistical significance of differences between groups was determined by non-parametric U-Mann-Whitney. Expected result was determined by the level of reliability p
Keywords: pacing; pulse pressure classes; drug therapy